In silico interaction of HOX cluster‐embedded microRNAs and long non‐coding RNAs in oral cancer. (16th August 2021) - Padam, Kanaka Sai Ram; Basavarajappa, Dhanraj Salur; Shenoy, U Sangeetha; Chakrabarty, Sanjiban; Kabekkodu, Shama Prasada; Hunter, Keith D.; Radhakrishnan, Raghu
Abstract: The essential role HOX‐associated non‐coding RNAs play in chromatin dynamics and gene regulation has been well documented. The potential roles of these microRNAs and long non‐coding RNAs in oral cancer development, with their attendant involvement in various cellular processes including proliferation, invasion, migration, epithelial–mesenchymal transition and metastasis is gaining credence. An interaction network of HOX‐embedded non‐coding RNAs was constructed to identify the RNA interaction landscape using the arena‐Idb platform and visualized using Cytoscape. The miR‐10a was shown to interact with HOXA1, miR‐10b with HOXD10, miR‐196a1 with HOXA5, HOXA7, HOXB8, HOXC8, HOXD8, and miR‐196a2 with HOXA5 . The lncRNAs, HOTAIR interacted with HOXC11, HOTAIRM1 with HOXA1 and HOXA4, HOTTIP with HOXA13, HOXA‐AS2 with HOXA3, HOXA11‐AS with HOXA11 and HOXD‐AS1 with HOXB8 . Changes in the HOX cluster‐embedded non‐coding RNAs have implications for prognosis and overall disease survival. Our review aims to analyze the functional significance and clinical relevance of non‐coding RNAs within the HOX cluster in the context of oral carcinogenesis. Elucidating these interactions between the non‐coding RNAs and HOX genes in oral cancer development and progression could pave the way for the identification of reliable biomarkers and potential therapeutic targets.